Association between the Diet Quality Index Adapted for Pregnant Women (IQDAG) and excess maternal body weight - Lívia Castro Crivellenti; Daniela Cristina Candelas Zuccolotto; Daniela Saes Sartorelli
Abstract Objectives: to investigate the relationship between the Diet Quality Index Adapted for Pregnant Women (IQDAG) and excess maternal body weight. Methods: a cross-sectional study was conducted with 754 adult pregnant women, in Ribeirão Preto, São Paulo, between 2011 and 2012. The criteria proposed by Atalah were used to classify the body mass index (BMI). Adjusted multinomial logistic regression models were employed to investigate the relationship between the IQDAG and being overweight and obese, estimating the odds ratio (OR) and the 95% confidence interval (CI95%). Results: the mean (SD) age of women was 28 (5) years, 33.4% were overweight and 25.6% obese. The pregnant women with higher scores in the IQDAG were less likely to be overweight [OR= 0.56 (CI95% = 0.37-0.85)] or obese [0.43 (0.26-0.71)]; those with higher scores in the "Fiber" [0.51 (0.33; 0.78)] and "Iron" [0.62 (0.40-0.96)] components were less likely to be overweight. However, women with higher scores in the percentage of energy from ultra-processed foods were more likely to be overweight [1.72 (1.10-2.94)] or obese [5.24 (2.80-9.80)], when compared to women with lower scores. Conclusions: poorer quality maternal diets were observed among the women who were overweight and obese during pregnancy.